Basin evolution of Upper Cretaceous–Lower Cenozoic strata in the Malargüe fold‐and‐thrust belt: northern Neuquén Basin, Argentina. (21st January 2015) - Balgord, Elizabeth A.; Carrapa, Barbara
Abstract: The Andean Orogen is the type‐example of an active Cordilleran style margin with a long‐lived retroarc fold‐and‐thrust belt and foreland basin. Timing of initial shortening and foreland basin development in Argentina is diachronous along‐strike, with ages varying by 20–30 Myr. The Neuquén Basin (32°S to 40°S) contains a thick sedimentary sequence ranging in age from late Triassic to Cenozoic, which preserves a record of rift, back arc and foreland basin environments. As much of the primary evidence for initial uplift has been overprinted or covered by younger shortening and volcanic activity, basin strata provide the most complete record of early mountain building. Detailed sedimentology and new maximum depositional ages obtained from detrital zircon U–Pb analyses from the Malargüe fold‐and‐thrust belt (35°S) record a facies change between the marine evaporites of the Huitrín Formation ( ca . 122 Ma) and the fluvial sandstones and conglomerates of the Diamante Formation ( ca . 95 Ma). A 25–30 Myr unconformity between the Huitrín and Diamante formations represents the transition from post‐rift thermal subsidence to forebulge erosion during initial flexural loading related to crustal shortening and uplift along the magmatic arc to the west by at least 97 ± 2 Ma. This change in basin style is not marked by any significant difference in provenance and detrital zircon signature. A distinct change in detrital zircons, sandstone composition and palaeocurrent direction from west‐directed to east‐directed occurs instead in the middle Diamante Formation and may reflect the Late Cretaceous transition from forebulge derived sediment in the distal foredeep to proximal foredeep material derived from the thrust belt to the west. This change in palaeoflow represents the migration of the forebulge, and therefore, of the foreland basin system between 80 and 90 Ma in the Malargüe area.